Penerapan Media Pembelajaran “Tree Chart” untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Tarikh Islam Kelas 3H di Pondok Modern Darussalam Gontor Ponorogo: Application of Learning Media " Tree Chart" to Improve Student Learning Outcomes for Tarikh Islam Lesson class 3H at Darussalam Modern Islamic Boarding School Gontor Ponorogo - Heru Saiful Anwar; Zuhrotul Mufidah; Mustabshirin Arrouf; Ajib Al-Murtadho (Educan, 2024)
One of the subject matters contained in Islamic education is Tarikh Islam. Tarikh Islam is one of the required lessons for students to be taught at Darussalam Modern Islamic Boarding School. This lesson teaches about Islamic history, including the stories of Rasulullah, Khulafaur Rashidin, the Companions of Rasulullah, and others. In teaching and learning activities, media is one of the important factors in learning. In view of the scores obtained by grade 3 H students in Islajn bn nb enmic date lessons, there are 20 out of 37 students, or 53% of students, who get scores below the passing score standard. This is due to the lack of innovation in learning activities, so that students become bored and do not pay attention to the lessons taught. And one of the innovations that can be used is with (Tree Chart) media learning. This study aims to improve student activeness and learning outcomes in Islamic date subjects in Class 3 H at Darussalam Modern Islamic Boarding School by using tree chart learning media. This type of research is classroom action research. In this study, researchers, acting as teaching teachers and assisted by an observer who supervises the condition of students, This research consists of the first cycle and the second cycle, which consist of: planning, implementation, observation, and reflection. Data collection techniques and tools in this study include using descriptive analysis techniques on data in the form of documentation of student learning outcomes, observation sheets, and test results. The results of this study show that (1) the application of tree chart learning media can increase student activity. With the presentation value of student activeness in the first cycle, which reached 61.37% and increased in the second cycle, which reached 84.12%, there was a difference between the first and second cycles, which reached 22.75%. (2) The application of tree chart learning media can improve student learning outcomes. The percentage of students who completed learning in the first cycle in the first cycle was 22 out of 37 students, or 59.45%, with an average score of 5.91, and in the second cycle, as many as 37 students, or 100%, with an average score of 7.78. With the explanation above, it can be concluded that tree chart learning media can increase student activeness and learning outcomes.